1995
DOI: 10.1073/pnas.92.18.8527
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calcium-independent phospholipase A2 prevents arachidonic acid incorporation and phospholipid remodeling in P388D1 macrophages.

Abstract: Cellular levels of free arachidonic acid (AA) are controlled by a deacylation/reacylation cycle whereby the fatty acid is liberated by phospholipases and reincorporated by acyltransferases. We have found that the esterification of AA into membrane phospholipids is a Ca2+-independent process and that it is blocked up to 60-70%o by a bromoenollactone (BEL) that is a selective inhibitor ofa newly discovered Ca2+-independent phospholipase A2 (PLA2) in macrophages.The observed inhibition correlates with a decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
270
3
9

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(295 citation statements)
references
References 32 publications
13
270
3
9
Order By: Relevance
“…BEL demonstrated a reduction of 12-HETE synthesis by 52% at the highest dose tested (30 μM). However, the results obtained with 30 μM BEL is likely not due to a specific inhibition of iPLA 2 , since other intact cell assays demonstrate IC 50 values of less than 5 μM BEL on arachidonic acid release or eicosanoid synthesis [53,60]. In line with this, the broken cell assay demonstrated that 30 μM BEL inhibited the conversion of exogenous arachidonic acid into 12-HETE by 42.1 ± 3.7%.…”
Section: Pcb-induced Arachidonic Acid Release In Human Platelets Is Mmentioning
confidence: 52%
“…BEL demonstrated a reduction of 12-HETE synthesis by 52% at the highest dose tested (30 μM). However, the results obtained with 30 μM BEL is likely not due to a specific inhibition of iPLA 2 , since other intact cell assays demonstrate IC 50 values of less than 5 μM BEL on arachidonic acid release or eicosanoid synthesis [53,60]. In line with this, the broken cell assay demonstrated that 30 μM BEL inhibited the conversion of exogenous arachidonic acid into 12-HETE by 42.1 ± 3.7%.…”
Section: Pcb-induced Arachidonic Acid Release In Human Platelets Is Mmentioning
confidence: 52%
“…It has traditionally been assumed that PL AA incorporation in activated cells may be secondary to the PLA 2 hydrolytic step because AA incorporates preferentially into the sn-2 position of PLs, and thus, for an enhanced AA reacylation to occur, 2-lysophospholipid acceptors, produced only by PLA 2 , should be provided. That lysophospholipid availability may limit AA reacylation in activated cells is also inferred from the finding that the specific activities of the enzymes of the reacylation pathway, ACSL and the CoA-dependent acyltransferases, are severalfold higher that that of PLA 2 in homogenates from resting and activated cells (23,(54)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, inhibition of iPLA 2 results in reduced levels of lysophospholipid acceptors, which in turn leads to a decreased incorporation of AA into PLs under unstimulated conditions (14,(23)(24)(25). When the effect of zymosan on AA incorporation was assayed in monocytes treated with BEL, and hence exhibiting diminished lysophospholipid levels (44), the response was slightly but significantly reduced (Fig.…”
Section: Stimulated Incorporation Of Aa Into Pls Of Activated Cells Imentioning
confidence: 99%
See 2 more Smart Citations